2013
DOI: 10.7241/ourd.20134.158
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune epidermal blistering diseases

Abstract: Autoimmune bullous skin diseases (ABDs) are uncommon, potentially fatal diseases of skin and mucous membranes which are associated with deposits of autoantibodies and complement against distinct molecules of the epidermis and dermal/epidermal basement membrane zone (BMZ). These autoantibodies lead to a loss in skin molecular integrity, which manifests clinically as formation of blisters or erosions. In pemphigus vulgaris, loss of adhesion occurs within the epidermis. The pioneering work of Ernst H. Beutner, Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 164 publications
1
7
0
Order By: Relevance
“…This is also in agreement with Xuefeng et al who found that most of PV cases (sensitivity 75%) and PF cases (sensitivity 66.7%) were positive for IgG4 immunostaining. In addition, Abreu‐Velez et al demonstrated IgG4 in 98% of pemphigus cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is also in agreement with Xuefeng et al who found that most of PV cases (sensitivity 75%) and PF cases (sensitivity 66.7%) were positive for IgG4 immunostaining. In addition, Abreu‐Velez et al demonstrated IgG4 in 98% of pemphigus cases.…”
Section: Discussionmentioning
confidence: 98%
“…An association between pemphigoid gestationis and IgG4 has also been documented. Some studies have demonstrated that IgG4 is less frequently found in the sera from patients with pemphigoid gestationis than IgG1 or IgG3 (9).…”
mentioning
confidence: 99%
“…When combined with immunosuppression, TPE is probably successful due to the pathogenesis of severe cases of dermatitis herpetiformis and herpes gestationis. 6064 Herpes gestationis or pemphigoid gestationis is an autoimmune subepidermal blistering disease that occurs in women in the second or third trimesters of pregnancy or even puerperium. It is a rare skin disease, the incidence of which has been estimated of approximately one case in every 40,000–60,000 pregnancies.…”
Section: Methodsmentioning
confidence: 99%
“…Although PV can emerge at any age, it is seen most often between the ages of 40 and 60 years. [ 5 ] In PF, the blisters are higher immediately below the stratum corneum in the epidermis and are associated with desmoglein 1, which is another cell surface adhesive molecule. [ 2 ] Of the 3 types, PF is the least severe.…”
Section: Introductionmentioning
confidence: 99%